2015
DOI: 10.1007/s11325-015-1155-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of excessive sleepiness is higher whereas insomnia is lower with greater severity of obstructive sleep apnea

Abstract: Both excessive sleepiness and insomnia were seen in high proportions of the patients referred on suspicion of OSA. Excessive sleepiness was higher whereas insomnia was lower with greater OSA severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 31 publications
5
57
2
Order By: Relevance
“…Only 13% of all of our male participants were classified as excessively sleepy using the Epworth Sleepiness Scale, which is consistent with population estimates from recent international literature 7 but considerably less than the 40% to 58% in patients referred to sleep clinics. 23 Sleepiness does not correlate well with OSA severity 24 and in our study the percentage of men with excessive sleepiness remained similar irrespective of the presence or severity of undiagnosed OSA. However, in the current study, the men with undiagnosed OSA and EDS have the highest likelihood of having depressive symptoms, in comparison with those with either condition alone.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Only 13% of all of our male participants were classified as excessively sleepy using the Epworth Sleepiness Scale, which is consistent with population estimates from recent international literature 7 but considerably less than the 40% to 58% in patients referred to sleep clinics. 23 Sleepiness does not correlate well with OSA severity 24 and in our study the percentage of men with excessive sleepiness remained similar irrespective of the presence or severity of undiagnosed OSA. However, in the current study, the men with undiagnosed OSA and EDS have the highest likelihood of having depressive symptoms, in comparison with those with either condition alone.…”
Section: Discussioncontrasting
confidence: 56%
“…EDS is considered a cardinal symptom of OSA and is also known to be associated with depression. 23,24 Due to the effect on daytime functioning, EDS is likely to be a factor in self-referral to a general practitioner for (A,B) AHI with or without EDS and (C,D) Epworth Sleepiness Scale scores with differing OSA severities split by type of depression questionnaire. *Presented probabilities are for a non-smoking, married man with median age (59 years) and waist circumference (99.3 cm), not suffering from either financial strain or erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown a positive correlation between AHI and the severity of depression [30, 53], we have demonstrated similar to Ong et al [29] that subjects with an AHI ≥15/h had a lower self-reported severity of depression than subjects with AHI <15/h, and that the self-reported severity of depression is not a risk factor for moderate to severe OSA. In addition, Bjorvatn et al [54] have shown that the prevalence of insomnia decreased when the severity of OSA increased, which enables better understanding of our results. Indeed, in our study, we have shown that both the lower severity of insomnia (only in univariate analysis) and the lower complaint of maintenance insomnia are associated with a greater risk of moderate to severe OSA.…”
Section: Discussionmentioning
confidence: 54%
“…Up to sixty percent of OSA patients can be excessively sleepy [30] and report higher rates of impaired concentration, mood lability, and other neurocognitive difficulties [31]. Epidemiologic studies demonstrate that excessive daytime sleepiness (EDS) modifies the relationship between AHI and incidence of hypertension [32], glucose metabolism [33], and mortality [34].…”
Section: Potential Clinically Relevant Osa Phenotypesmentioning
confidence: 99%